To substitute or not? A systematic review of immunoglobulin replacement therapy in multiple myeloma patients treated with bispecific antibodies - Paulsen, Juni Songe; Slørdahl, Tobias S. (Frontiers in Immunology, 2026)
Bispecific antibodies are a novel class of immunotherapies that have demonstrated high response rates in heavily pretreated patients with multiple myeloma. However, their use is associated with increased risk of infections, which contribute to morbidity and mortality. Current guidelines recommend immunoglobulin replacement therapy for patients receiving bispecific antibodies with polyclonal IgG levels below 4 g/L, in addition to prophylactic antimicrobial therapy, to reduce infection risk. This systematic review aimed to evaluate the effect of immunoglobulin replacement therapy in multiple myeloma patients treated with bispecific antibodies. Through a structured literature search, we identified five retrospective, non-randomized cohort studies comprising a total of 653 patients. Three of these studies reported a significant reduction in infections, particularly severe infections, among patients receiving immunoglobulin replacement therapy. Given the substantial time and resource burden associated with continuous immunoglobulin prophylaxis for both patients and healthcare systems, further prospective, randomized studies are needed to confirm these findings and guide evidence-based practice.